Confocal Imaging with a Fluorescent Bile Acid Analogue Closely Mimicking Hepatic Taurocholate Disposition. Issue 6 (20th March 2014) - De Bruyn, Tom; Sempels, Wouter; Snoeys, Jan; Holmstock, Nico; Chatterjee, Sagnik; Stieger, Bruno; Augustijns, Patrick; Hofkens, Johan; Mizuno, Hideaki; Annaert, Pieter
<x xml:space="preserve">Abstract</x> This study aimed to characterize the in vitro hepatic transport mechanisms in primary rat and human hepatocytes of the fluorescent bile acid derivative N‐(24‐[7‐(4‐N, N‐dimethylaminosulfonyl‐2, 1, 3‐benzoxadiazole)]amino‐3α, 7α, 12α‐trihydroxy‐27‐nor‐5β‐cholestan‐26‐oyl)‐2′‐aminoethanesulfonate (tauro‐nor‐THCA‐24‐DBD), previously synthesized to study the activity of the bile salt export pump (BSEP). The fluorescent bile acid derivative exhibited saturable uptake kinetics in suspended rat hepatocytes. Hepatic uptake was inhibited in the presence of substrates/inhibitors of the organic anion transporting polypeptide (Oatp) family and Na+‐taurocholate cotransporting peptide (Ntcp). Concentration‐dependent uptake of the fluorescent bile acid was also saturable in Chinese hamster ovary cells transfected with rNtcp, hNTCP, OATP1B1, or OATP1B3. The fluorescent bile acid derivative was actively excreted in the bile canaliculi of sandwich‐cultured rat and human hepatocytes (SCRH and SCHH), with a biliary excretion index (BEI) of 26% and 32%, respectively. In SCRH, cyclosporin A significantly decreased the BEI to 5%. Quantification by real‐time confocal imaging further confirmed canalicular transport of the fluorescent bile acid derivative (BEI = 75%). We conclude that tauro‐nor‐THCA‐24‐DBD is a useful probe to study interference of drugs with NTCP/Ntcp‐ and BSEP/Bsep‐mediated transport in fluorescence‐based in vitro assays. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci